339 The Glasgow Lumbar Spinal Stenosis Scale: An Individualised Measurement Formula for the Radiological Assessment of Lumbar Spinal Stenosis. (12th October 2021) - Bradley, R; Kumar, A; Barrett, C
Abstract: Background: Lumbar spinal stenosis (LSS) is a common spinal problem. Currently there is no universally accepted quantitative approach to the radiological measurement of LSS. Quantitative descriptions do exist, but these are unidimensional and do not consider normal variation in anatomy. We propose a universal and individualised measurement system for the quantitative radiological assessment of lumbar spinal stenosis. Method: A retrospective case series of patients who had undergone surgery for symptomatic lumbar spinal stenosis over a 3-year period. Pre-operative T2 weighted lumbar spine MRI were analysed. Each patient had the degree of lumbar canal stenosis quantified using our approach. Results: Our novel formula for the quantitative radiological assessment of LSS is two dimensional, repeatable, and presented as a percentage, to correct for the individual patient. The surface area of the canal at the level of stenosis is measured (mm2). The adjacent 2 levels are then measured and averaged. The calculation becomes (A-S/A) x 100 = R, where S is the canal surface area at the stenosed level, A is the average canal surface area of the two levels adjacent to the level of interest and R is the relative degree of lumbar spinal canal stenosis expressed as a percentage. Conclusions: This novel quantitative measurement formula for the radiological assessment of lumbar canal spinal stenosis is quick and simple to calculate and most importantly adjusts for the individual patient's normal or degenerative anatomy. This new measurement tool will need validation against specific clinical and operative criteria in the future.